(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper analyses the meaning, content and application of the fourth rule ofArticle 8 of the Spanish Criminal Code. This precept tries to resolve the conflicting norms in relation to alternativity, i.e. in cases in which a number of norms appear tobe applicable, but in which only one is finally applied, the one which establishes themost severe sentence.